Evolution and genetic differentiation among relatives of Arabidopsis thaliana - Koch, Marcus; Matschinger, Michaela (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Arabidopsis thaliana is one of the most intensively studied plant species. More recently, information is accumulating about its closest relatives, the former genus Cardaminopsis. A. thaliana diverged from these relatives, actually treated within three major lineages (Arabidopsis lyrata, Arabidopsis halleri, and Arabidopsis arenosa), ≈5 mya. Significant karyotype evolution in A. thaliana with base chromosome number reduction from x=8 to x=5 might indicate and favor effective genetic isolation from these other species, although hybrids are occurring naturally and have been also constituted under controlled conditions. We tested the evolutionary significance to separate the x=5 from the x=8 lineage using DNA sequence data from the plastome and the nuclear ribosomal DNA based on an extensive, representative worldwide sampling of nearly all taxonomic entities. We conclude that (i) A. thaliana is clearly separated phylogenetically from the x=8 lineage, (ii) five major lineages outside A. thaliana can be identified (A. lyrata, A. arenosa, A. halleri, Arabidopsis croatica, and Arabidopsis pedemontana) together with Arabidopsis cebennensis, and (iii) centers of genetic and morphological diversity are mostly in congruence and are located close to the Balkans in Austria and Slovakia outside glaciated and permafrost regions with few notable exceptions.
Gesehen am 08.05.2017